2014
DOI: 10.1111/tpj.12704
|View full text |Cite
|
Sign up to set email alerts
|

The CRISPR/Cas system can be used as nuclease for in planta gene targeting and as paired nickases for directed mutagenesis in Arabidopsis resulting in heritable progeny

Abstract: These authors contributed equally to this work. SUMMARYThe CRISPR/Cas nuclease is becoming a major tool for targeted mutagenesis in eukaryotes by inducing double-strand breaks (DSBs) at pre-selected genomic sites that are repaired by non-homologous end joining (NHEJ) in an error-prone way. In plants, it could be demonstrated that the Cas9 nuclease is able to induce heritable mutations in Arabidopsis thaliana and rice. Gene targeting (GT) by homologous recombination (HR) can also be induced by DSBs. Using a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
265
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 331 publications
(273 citation statements)
references
References 66 publications
5
265
1
2
Order By: Relevance
“…Using the same method, we found that, among accessions included in field experiments, the three loci and their interactions explained nearly 36% of the variation in overall GSL profile among accessions. Recent genome-editing techniques may allow formal testing of fitness effects of combinations of GSL alleles in the future (37).…”
Section: Significancementioning
confidence: 99%
“…Using the same method, we found that, among accessions included in field experiments, the three loci and their interactions explained nearly 36% of the variation in overall GSL profile among accessions. Recent genome-editing techniques may allow formal testing of fitness effects of combinations of GSL alleles in the future (37).…”
Section: Significancementioning
confidence: 99%
“…So far, reports about CRISPR-assisted knock-in experiments in plants describe circular donor templates ranging from 0.47 to 5.2 kb in total length, including homology sequences of 46 bp to 1.6 kb on each side of the sequence of interest [2,6,8,10,43,67,68] ( Table 1). As for free DNA fragments, they varied from 72 to 476 bp including homology arms, of even length or not, of 46 to 146 bp [6,11,67,69].…”
Section: With Homology To the Targetmentioning
confidence: 99%
“…Regarding the donor DNA, long donor templates (with long sequences of interest or long homology arms) can be delivered to the cells on the same or on another plasmid as the CRISPR-Cas system [2,6,8,27,41,69], or as linear dsDNA fragments, provided as free molecules [67] or released in planta from a plasmid by inserting them between CRISPR target sites [3,10,67]. Shorter templates (with short homology arms or small replacement sequences) can be introduced into the cells as ssDNA oligonucleotides (sense or antisense) [6,11,67,75].…”
Section: Type Of Delivered Moleculesmentioning
confidence: 99%
See 2 more Smart Citations